Manajemen Pengembangan Dakwah pada Yayasan Daarul Armina Kota Bengkulu - Ahmad Rafiezal Maizan; Wildan Yahya; Asep Ahmad Siddiq (UNISBA Press, 2024)
Abstract. As a da'wah institution, the foundation must have good management in carrying out da'wah development. This can maximize the development of da'wah at the foundation. This research is entitled